2016
DOI: 10.1111/bjh.14407
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 trial of high dose lenalidomide in patients with relapsed/refractory higher‐risk myelodysplastic syndromes and acute myeloid leukaemia with trilineage dysplasia

Abstract: Limited therapies exist for patients with refractory and relapsed (RR) higher-risk myelodysplastic syndromes (HR-MDS) and acute myeloid leukaemia with trilineage dysplasia (AML-TD). High dose (HD) lenalidomide (50 mg) has activity as frontline therapy in elderly AML but there is limited data in the RR setting. This phase II trial included patients with RR HR-MDS or AML-TD at 2 doses of lenalidomide (15 or 50 mg) on days 1-28 of 42-day cycles. The primary endpoint was response rate using the 2006 International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
0
14
1
1
Order By: Relevance
“…In highrisk MDS after HMA failure, treatment with standard-(15 mg) or high-dose (50 mg) lenalidomide resulted in scarce/absent clinical activity and extreme toxicity. 56 However, there are reports of higher response rates (40%) in HMA-refractory MDS patients, with CR in those carrying del5q. 57 High doses of lenalidomide induced mCR in 33% and HI in 8% of HMA-refractory patients.…”
Section: Management Of Hma Failuresmentioning
confidence: 99%
“…In highrisk MDS after HMA failure, treatment with standard-(15 mg) or high-dose (50 mg) lenalidomide resulted in scarce/absent clinical activity and extreme toxicity. 56 However, there are reports of higher response rates (40%) in HMA-refractory MDS patients, with CR in those carrying del5q. 57 High doses of lenalidomide induced mCR in 33% and HI in 8% of HMA-refractory patients.…”
Section: Management Of Hma Failuresmentioning
confidence: 99%
“…The findings herein suggest that small-molecule inhibitors targeting aberrant biological pathways can produce antiproliferative effects in otherwise refractory leukemia cells. Drugs with apparently low efficacy using this ex vivo methodology, such as venetoclax and lenalidomide, may be effective clinically, however, as combination treatment or in specific disease subsets (34,52). An assay with viability as the read-out may underestimate the efficacy of drugs with noncytotoxic mechanisms of action.…”
Section: Medical Sciencesmentioning
confidence: 99%
“…Given the successful application of lenalidomide in low and intermediate‐1 risk MDS, several trials have examined the potency of lenalidomide monotherapy in intermediate‐2 and HR‐MDS (Table ) . In a phase 2 study, low dose lenalidomide (10 mg) was shown to result in transfusion independence in 26% of patients with intermediate‐2 and HR‐MDS with 5q− (Table ) .…”
Section: Clinical Efficacy Of Lenalidomidementioning
confidence: 99%
“…Encouraged by these results, a phase 2 clinical trial recently examined the efficacy of even higher doses of lenalidomide (15 mg and 50 mg) in patients with HR‐MDS and AML with trilineage dysplasia . Unfortunately, only a minority of patients had a clinical response at the cost of high rates of toxicity (Table ).…”
Section: Clinical Efficacy Of Lenalidomidementioning
confidence: 99%